The Relationship between Stress Level, Physical Activity Level and Dietery Habit with Hypertension Incidence - Taufik Septiawan; Nunung Herlina; Devi Ariani Ardy; Indrawan Kholistiyanto; Firda Ummi (Indonesian Journal of Global Health Research, 2022)
Hypertension is a major risk factor for death in the world. Hypertension is strongly influenced by the way and habits of a person's life which is often referred to as the killer disease because people with hypertension do not know if they have hypertension There are many risk factors for the incidence of hypertension, including consuming foods that contain a lot of salt and fat, not eating enough fruits and vegetables, consuming excessive alcohol, lack of physical activity, and poor stress management. researchers are interested in conducting research on the relationship between stress levels, physical activity and dietery habits with hypertension Incidence. The research design used quantitative analytic with a cross-sectional approach. Instruments for measuring blood pressure using a digital sphygmomanometer, measuring stress levels using the standard DASS (Depression Anxiety Stress Scale), measuring activity levels using the standard IPAQ (International Physical Activity Questionnaire), and measuring Dietery Habits or eating pattern using a diet questionnaire that has been modified and has been tested for validity, reliability, and normality. Data analysis using the Chi-square test. The Result Showed that there was a relationship between Stress level, Phsycal Activity, and dietery habit with hypertension Incidence.